2006
DOI: 10.1007/s00467-006-0272-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tonsillectomy pulse therapy versus multiple-drug therapy for IgA nephropathy

Abstract: We evaluated the efficacy of tonsillectomy plus pulse prednisolone, warfarin, and dipyridamole including methylprednisolone pulse (tonsillectomy plus pulse therapy), versus prednisolone, warfarin, and dipyridamole including mizoribine (PWDM) for the treatment diffuse IgA nephropathy (IgAN) in children. The patients were randomly assigned to be treated by tonsillectomy plus pulse therapy for 2 years (Group A, n=16) or PWDM for 2 years (Group B, n=16). The clinical features and pathological findings in both grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 14 publications
(26 reference statements)
0
30
0
1
Order By: Relevance
“…Masuda et al (1988) observed improvement on urinalysis in all of seven Japanese children with IgAN who underwent tonsillectomy. In addition, we previously reported that that tonsillectomy pulse therapy is as effective as PWD with mizoribine in ameliorating proteinuria and histological severity as an initial treatment in IgAN patients and in preventing acute exacerbation of IgAN by tonsillitis, although no untreated control group has included in that study (Kawasaki et al 2006). However, no reports on the efficacy of tonsillectomy pulse therapy as rescue treatment for steroid-resistant IgAN in childhood have been available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Masuda et al (1988) observed improvement on urinalysis in all of seven Japanese children with IgAN who underwent tonsillectomy. In addition, we previously reported that that tonsillectomy pulse therapy is as effective as PWD with mizoribine in ameliorating proteinuria and histological severity as an initial treatment in IgAN patients and in preventing acute exacerbation of IgAN by tonsillitis, although no untreated control group has included in that study (Kawasaki et al 2006). However, no reports on the efficacy of tonsillectomy pulse therapy as rescue treatment for steroid-resistant IgAN in childhood have been available.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis showed that approximately 60% of their patients who underwent tonsillectomy pulse therapy achieved remission of urinary abnormalities (Hotta et al 2001). We also reported that tonsillectomy pulse therapy was effective as an initial treatment for IgAN in pediatric patients (Kawasaki et al 2006). However, there have been no reports on the efficacy of tonsillectomy pulse therapy as rescue treatment for steroid-resistant IgAN in childhood.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, based on a mata -analysis, Liu et al reported that tonsillectomy may induce clinical remission and reduce the rate of progression to end -stage renal disease in patients with IgAN 17,18) . We also reported that TMP as an initial therapy for pediatric IgAN was effective in a short -term follow -up study 15) . Our case presented herein further suggest that TMP was effective as a rescue therapy for recurrent severe IgAN after multi -drug combination therapy.…”
Section: Discussionmentioning
confidence: 73%
“…Hotta et al reported that tonsillectomy plus methylprednisolone pulse therapy led to clinical remission in adult patients with IgAN (Hotta et al 2001). In addition, we reported that tonsillectomy pulse therapy was effective for severe IgAN in childhood (Kawasaki et al 2006). Wyatt and Hogg (2001), on the other hand, claimed that tonsillectomy cannot be recommended for IgAN by evidence-based criteria.…”
Section: Discussionmentioning
confidence: 99%